Evaluation of the antiamnesic effects of Phyllanthus amarus in mice. (Colombia Medica, 2007)
Alzheimer’s disease is a progressive neurodegenerative disorder characterized by a gradual decline in memory. Phyllanhus amarus is commonly known as bhumi amla in India and is traditionally used since centuries in ayurveda medicine. The present study was undertaken to investigate the effects of Phyllanhus amarus (PA) on cognitive functions and brain cholinesterase activity in mice. Elevated plus maze and passive avoidance paradigm were employed to evaluate learning and memory parameters. Three doses (50, 100 and 200 mg/kg, p.o.) of aqueous extract of PA were administered for 8 successive days to both young and aged mice. PA (50, 100 and 200 mg/kg) produced a dose-dependent improvement in memory scores of young and older mice. PA also reversed successfully the amnesia induced by scopolamine (0.4 mg/kg, i.p.) and diazepam (1 mg/kg, i.p.). Interestingly, brain acetyl cholinesterase activity was also reduced. The underlying mechanism of action for the observed nootropic effect may be attributed to pro-cholinergic activity exhibited by PA in the present study. Therefore, it would be worthwhile to explore the therapeutic potential of PA in the management of patients with cognitive disorders.